Pendidikan Politik Perempuan bagi Kelompok PKK sebagai Upaya Pemenuhan Hak Konstitusional Warga Negara di Desa Ledug Kecamatan Kembaran - Sari, Yunita Ratna; Nurafifah, Lestiana Dita; Sari, Ayu Fatika; Al Wafi, Salma Rasyida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of this Community Service is to provide knowledge on how to be a smart and wise voter, the procedures for casting votes in the polling station, and the rights of citizens as regulated in the 1945 Constitution so that the PKK group in Ledug Village has political insights and awareness. The Community Service method is carried out through political socialization to women face-to-face, starting from preparation, briefing, to implementation. This service activity is carried out directly by lecturers and students from UIN Prof.K.H.Saifuddin Zuhri Purwokerto. The expected end result of this Community Service is to provide significant benefits to the PKK group in Ledug Village, so that they understand how to cast votes in the polling station, do not abstain from voting, and can actively participate in the Village Head Election 2023 and the General Election 2024.